Cybersecurity for commercial vehicles - D'Anna, Gloria (SAE International, 2019)
This book explores the cybersecurity challenges facing modern commercial vehicles, such as trucks and buses, as they become increasingly connected and computerized. It explains how vehicle systems can be vulnerable to cyberattacks, outlines risk assessment methods, and presents security strategies to protect vehicle networks and data.